Control potency of Trans-cinnamic acid and antifungal metabolites of Xenorhabdus szentirmaii against Alternaria brassicicola - Barış Gülcü; Nedim Altın (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
The, antifungal activities of trans-cinamic acid (TCA) and cell-free supernatant (CFS) of X. szentirmaii were evaluated against Alternaria brassicicola that cause Black spot disease. The results showed that TCA was more suppressive than CFS of X. szentirmaii in the control of A. brassicicola. In petri assays, the highest suppressive effect on spore germination was in TCA treatments compared to CFS of X. szentirmaii. Moreover, no germ tube elongation was observed in any of tested concentrations (0.25%, 0.50%, 1%, 2%) of TCA. The highest level of mycelial growth inhibitions (100% and 92%) were exhibited by TCA (2%) and TCA (1%), respectively. The curative and protective activity of TCA on disease severity of A. brassicicola were also evaluated on broccoli plants. In the curative activity assays, disease severities were 71.00%, 56.33% and 54.03% for control, TCA (1%) and TCA (2%), respectively. Whereas in the protective activity, TCA (2%) suppressed the disease severity significantly greater than TCA (1%). The disease severity of A. brassicicola after TCA application on broccoli plants was 25.21% and 17.37% for TCA (1%) and TCA (2%) respectively. Similar data were obtained in the efficacy of TCA on A. brassicicola. In the curative activity assays, TCA (1%) and TCA (2%) exhibited the efficacy with rates of 20.57% and 23.02%, respectively. However, TCA (2%) showed significantly higher efficacy than TCA (1%) in the protective activity. The current study provides that TCA has a great potential to suppress A. brassicicola and can be a good alternative to synthetic fungicides.